Scientific texts writing: a didactic debate focused on meaningful learning - Maria da Conceição Barbosa Mendes (Universidade Federal do Oeste da Bahia, 2020)
This dissertation results from our attention as teacher of the Research Methodology in Education curricular unit, relatively to the elaboration of scientific essays at the Higher Institute of Education Sciences of Benguela. The study proposes to discuss the structure of didactic-pedagogical scenarios that promote the understanding of the underlying logic of scientific writing and its exercising. Its implementation involved the mobilization and link of the presuppositions of meaningful learning and didactic foundations of the three-dimensionality of the learning content. This is a descriptive study, resulting from the action-research-action logic in which bibliographic research, documentary analysis, questionnaire inquiry and expert consultation substantiated by qualitative content analysis procedures conformed our approach. From this, we assess the pertinence of the curricular unit and the structuring and sequencing of didactic scenarios based on logics embodied in the construction of knowledge inherent in the writing of scientific essays.